TEACHING READING THROUGH SHARED READING STRATEGY - riza, armilia (TELL - US JOURNAL, 2016)
This study was aimed at looking at the effect of using Shared Reading Strategy toward reading ability of students of SMP N 1 IV Jurai Pesisir Selatan, West Sumatra. This study is based on the fact the poor ability of students to understand the monologue text. This study used pretest-posttest design given to the experimental and control groups. The results showed that the experimental group posttest result was higher than the control group. It showed that the Shared Reading Strategy gave significant effect toward students’ reading ability at SMP N 1 IV Jurai. This statement is supported by the results of t test with significant value of 2.26.